Relation Ship and Effect Of Jet Stream in Anti-Ciyclone in Influencing The Climate Of Iraq (Journal of the College of Education for Women, 2019)
This study aimed to statement jet stream and its impact in the anti-cyclone affecting the climate of Iraq. Through the use of simple correlation coefficient ( Pearson ) that there is a very strong relationship between high- Siberian and both of the jet stream especially during the winter or over the stations of North . Therefore we, observe the relationship be significant in most of the winter months , spring and autumn . Statistically significant , but are different between station and another station , while the study come to another Anti-ciyclon have a real ,significant and statistically relationship corrclation . But this relationship is less than which found in are much less it with the Siberian high , it depends on the type of station and the month type in which the recurring phenomenon, So this study concluded that the current affects in the minimum temperature for Anti-ciclon which accompanying the streams jet every one as its type and varying degrees, temperatures drop in general when accompany anti-ciyclon air polar jet stream and especially during the winter months because of its cold mass with notice some exceptions , especially during some months, with high temperatures